Characterization of beach run-up patterns in Bagnoli bay during ABBACO project. Issue 6 (2nd July 2020) - Di Luccio, D.; Benassai, G.; Mucerino, L.; Montella, R.; Conversano, F.; Pugliano, G.; Robustelli, U.; Budillon, G.
ABSTRACT: This paper reports the results of an integrated atmospheric and wave run-up forecasting system, validated with in situ measured data, for the coastal site of Bagnoli, inside the Gulf of Pozzuoli, in the Thyrrenian Sea. A modelling chain consisting of Weather Research and Forecasting model, Wave Watch 3 model and a run-up calculator was used to obtain the R u 2 % levels on the beach of Bagnoli, in the framework of the rehabilitation project of the industrial site. Hindcasted waves were validated with observed ones in intermediate depth, while run-up excursions were validated using video-monitoring system located on the beach. The run-up observations were obtained by time stack images analysed using video-monitoring system. An error compensation algorithm was implemented for the correction of the systematic deviations from the DGPS more precise measurements. Among the different schemes chosen for wave run-up prediction, the one of Stockdon et al. [Empirical parameterization of setup, swash, and runup. Coast Eng. 2006;53(7):573–588] was found to be outperforming in matching with the observed run-up levels. This result was expected because of the structure of this formula, which takes into account both the set-up and swash run-up contributions.